مدى فعالية معايير التكلفة المطورة في البيئة التصنيعية الحديثة - دراسة تطبيقية – - فخر, نواف; شيخ محمد, حسين; جديد, غيث محمد (Latakia University Journal - Economic and Legal Sciences Series, 2014)
تمثل معايرة التكاليف الجانب الأساس في عملية البناء لأي نظام تكاليف معيارية متكامل, وانطلاقاً من ذلك, تلقى عملية معايرة التكاليف أهمية خاصة في مجال التخطيط والرقابة واتخاذ القرارات. إن الانتقادات التي وجهت إلى معايير التكلفة في البيئة التقليدية, لا تعني أن تلك المعايير يجب التخلي عنها في البيئة التصنيعية الحديثة, وإنما يجب تطويرها لكي تعكس المتغيرات التكنولوجية والتنافسية, و عليه، جعلها أكثر كفاءة وفعالية, ذلك لأن التحديد المسبق والجاري لما يجب تحقيقه, ولما يجب أن يكون, ثم متابعة الأداء وقياس ما تم تحقيقه, ومقارنته مع ما كان مستهدفاً, وتحديد الانحرافات وأسبابها, كل ذلك لا يمكن التقليل من أهميته ودوره في زيادة فعالية الرقابة وتقويم الأداء. وهنا يتناول الباحث كيفية تطوير معايير التكلفة في ظل المتغيرات البيئية الحديثة والمتمثلة في عالمية المنافسة وتكنولوجيا التصنيع الحديثة, ولتحقيق الهدف من البحث, قام الباحث بدراسة الأفكار التالية: أولاً: تحديد الأهداف التي يجب على معايير التكلفة أن تخدمها في بيئة التصنيع الحديثة. ثانياً: دراسة الخصائص المقترحة التي يجب أن تكتسبها المعايير في ظل البيئة التصنيعية الحديثة. ثالثاً: خطوات إعداد المعايير في ظل البيئة التصنيعية الحديثة. Cost standards represent the main part of the building process of any complete standard cost system. Given this, the cost calibration process attracts special attention in the domains of planning, control, and decision making. The criticisms directed to standard costing systems in the traditional environment do not mean that these systems must be abandoned in the modern industrial environment, but they must be developed to reflect the competitive and technological changes, making them more competent and effective. That is, the past and present determination for what it must achieve, and what it must be, then for performance continuation and measuring what has been achieved, and comparing it with what was set, and determining variances and their reasons, can't reduce its importance and role in increasing the effectiveness of control and evaluation of performance. The researcher discusses how to develop cost standards in the light of modern environmental changes represented in international competition and the technology of modern industry. To achieve the objective of this research, the researcher studies the following points: Determining aims that these cost standards must serve in the environment of modern industry. Studying the proposed characteristics that these cost standards must acquire in the light of the modern industrial environment. Steps of standard preparation in the light of the modern industrial environment.